Faktor-Faktor yang Berhubungan dengan Kejadian Stunting Pada Balita di Kelurahan Tunjung Teja Kecamatan Tunjung Teja Kabupaten Serang Provinsi Banten - Gapmelezy, Ezzy; Komalasari, Dwi (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT According to data from the toddler cohort at 4 Posyandu, Tunjung Teja District for the period January 2024 to June 2024, it was recorded that of the 172 toddlers aged 6-59 months who regularly attended posyandu, there were 39 (22.6%) toddlers whose height was below -2SD or included in the category stunting. Therefore, the author is interested in knowing the factors related to the incidence of stunting among toddlers in Tunjung Teja Village, Tunjung Teja District, Serang Regency, Banten Province in 2024. To find out the factors related to the incidence of stunting in toddlers. This type of research is descriptive analytical, using a cross sectional research design, and using Chi Square test analysis, conducted in June 2024 with a population of 172 toddlers aged 6 months to 59 months, a sample of 120 toddlers with a simple random sampling technique, tools Data collection for the dependent variable is a microscopic measuring instrument, measuring Body Length (PB) and Body Height (TB) with an accuracy of 0.1 cm, independent variables using interview and documentation techniques. Univariate and Bivariate data analysis using the chi square statistical test. The results of the study showed that of the 120 respondents who experienced stunting, 63 were toddlers (52.5%), from the 4 variables studied, the results showed that there was a relationship between history of exclusive breastfeeding, a p-value of 0.012 and an Odd Ratio (OR) value of 0.363. 363 means toddlers who did not receive breast milk Exclusives have a 0.363 times chance of experiencing stunting compared to toddlers who receive exclusive breast milk. Infectious Diseases p-value 0.000 and OR 4.038 means that toddlers who have a history of infectious diseases have a 4.038 times chance of experiencing stunting compared to toddlers who do not have a history of infectious diseases. Immunization History Basic p-value of 0.001 and OR 0.202 means that toddlers who have never been immunized have a 0.202 chance of experiencing stunting compared to toddlers who have been immunized. Maternal Education p-value 0.020 and OR 2.560 means that mothers with low education have a 2.560 times chance of having stunted children compared to mothers with higher education. There is a relationship between the variables Exclusive Breastfeeding, Infectious Diseases, Complete Basic Immunization History, Mother's Education and the incidence of stunting in toddlers. This research suggests that mothers can provide exclusive breast milk, maintain children's health so they do not experience infectious diseases, and provide complete basic immunization. Keywords: Exclusive Breastfeeding, Infectious Diseases, Complete Basic Immunization History, Maternal Education, Stunting.  ABSTRAK Menurut data kohort balita di  4 Posyandu Kelurahan Tunjung Teja periode Januari 2024 sampai Juni 2024, tercatat dari 172 balita berusia 6-59 bulan yang rutin mengikuti posyandu terdapat 39 (22,6%)  balita yang tinggi badan nya di bawah -2SD atau termasuk kategori stunting. Oleh karena itu penulis tertarik untuk mengetahui faktor-faktor yang berhubungan dengan kejadian stunting pada balita di Kelurahan Tunjung Teja Kecamatan Tunjung Teja Kabupaten Serang Provinsi Banten Tahun 2024. Untuk mengetahui faktor-faktor yang berhubungan dengan kejadian stunting pada balita. Jenis Penelitian ini adalah deskriptif analitik, menggunakan design penelitian cross sectional, dan menggunakan analisis uji Chi Square, dilakukan pada bulan Juni 2024 dengan jumlah populasi 172 balita berusia 6 bulan sampai 59 bulan,  sampel 120 balita dengan teknik pengambilan sampel secara simple random sampling, alat pengumpulan data variable dependen adalah alat ukur mikrotois, pengkuran Panjang Badan (PB) dan Tinggi Badan (TB) dengan ketelitian 0,1 cm, variable independen dengan teknik wawancara dan dokumentasi. Analisa  data univariat dan Bivariat dengan uji statistic chi square. Hasil penelitian menunjukan dari 120 responden yang mengalami stunting sebanyak 63 Balita (52,5%), Dari 4 variabel yang diteliti didapatkan hasil ada hubungan  Riwayat ASI Ekslusif p-value 0,012 dan nilai Odd Rasio (OR) 0,363 berarti balita yang tidak mendapatkan ASI ekslusif mempunyai peluang 0,363 kali mengalami stunting dibandingkan balita yang mendapatkan ASI  ekslusif. Penyakit Infeksi p-value 0,000 dan OR 4,038 berarti balita yang mempunyai riwayat penyakit infeksi mempunyai peluang 4,038 kali mengalami stunting dibandingkan balita yang tidak mempunyai riwayat penyakit infeksi. Riwayat Imunisasi Dasar Lengkap p-value 0,001 dan OR 0,202 berarti Balita yang tidak pernah di imunisasi mempunyai peluang 0,202 kali mengalami stunting dibandingkan balita yang pernah di imunisasi. Pendidikan Ibu p-value 0,020 dan OR 2,560 berarti ibu dengan pendidikan rendah mempunyai peluang 2,560 kali mempunyai anak stunting dibandingkan ibu dengan pendidikan tinggi. Terdapat hubungan antara variabel ASI Ekslusif, Penyakit Infeksi Riwayat Imunisasi Dasar Lengkap, Pendidikan Ibu dengan kejadian stunting pada balita. Penelitian ini menyarankan agar ibu dapat memberikan ASi ekslusif, menjaga kesehatan anak agar tidak mengalami penyakit infeksi, memberikan imunisai dasar secara lengkap. Kata Kunci: ASI Ekslusif, Penyakit Infeksi, Riwayat Imunisasi  Dasar Lengkap, Pendidikan Ibu, Stunting